Kekuatan Hukum Akta Hibah Atas Tanah dan Bangunan Menurut Hukum Perdata (Studi Kasus Putusan Nomor: 236/PDT/G/2022/PN. BKS) - Kevin Kurniawan; Hanafi Tanawijaya (LPPM Universitas Ekasakti Padang, 2023)
In making grants of land and buildings according to civil law, it is regulated in the Civil Code (KUHPerdata) article 1666 which states that a gift is an agreement where the donor gives a gift while still alive to the recipient of the gift free of charge and cannot be withdrawn. return, hand over an object for the purposes of the recipient of the gift who receives the delivery of the object, in general to make a gift of land and buildings by making a deed of gift to the PPAT, the making of this deed of gift is attended by the parties, in this case the giver and recipient of the gift and witnessed by at least 2 (two) witnesses who meet the requirements, then the grant deed is registered at the Land Office, pays taxes, namely Income Tax (PPh) and BPHTB on the grant, then transfers the name of the certificate to the Land Office based on the grant. The type of research used in this research is normative. To support this research, the author used a library research type of research, which examined several documents related to this research. The method in this research is a normative method with a statutory regulatory approach. Research data shows the strength of the Deed of Grants for Land and Buildings According to Civil Law (Case Study of Bekasi District Court Decision Number 236/PDT.G/2022/PN.BKS).